Evaluation of Cytokine Profile in Canine Malignant Oral Melanoma - Carmen G. Pérez-Santana; Sara E. Cazorla-Rivero; Ana A. Jiménez-Alonso; Francisco Rodríguez-Esparragón; Jesús María González Martín; Ruth Henríquez-Cabrera; Bernardino Clavo-Varas; Enrique Rodríguez Grau-Bassas (Veterinary Sciences)
Ten dogs with oral malignant melanoma were evaluated and treated with surgery, of which four dogs were diagnosed with melanotic melanoma and six were diagnosed with amelanotic melanoma. Serum samples from oral malignant melanoma (OMM) were collected at baseline, the day of the surgery, and every 3–4 months, during which time a clinical examination and chest X-rays were performed. Concentrations of GM-CSF, IFN-γ, IL-2, IL-6, IL-7, IL-8, IL-10, IL-15, IL-18, IP-10, KC-like, MCP-1, and TNFα were quantified. Follow-up samples indicated that after the removal of malignant melanoma, the serum levels of GM-CSF, IFN-γ, MCP-1, IL-18, and IL-2 increased significantly. In contrast, when comparing samples from dogs with OMM to those of patients in remission, the concentrations of IL-7 and MCP-1 were significantly higher in the remission samples than in the OMM samples. Furthermore, when comparing the serum concentrations between the OMM-metastasis samples and those patients in remission, elevated levels of MCP-1 were associated with poorer overall survival due to the development of OMM metastasis. Finally, a comparison of cytokines in the melanotic OMM and amelanotic OMM samples revealed that the amelanotic OMM samples exhibited higher concentrations of IL-6, IL-10, and IL-15 compared to the melanotic OMM samples.